Educational Justice: Inequality in Pagedongan and Pandanarum, Banjarnegara - Muhammad Faiz Azmi (Jurnal Studi Ilmu Sosial dan Politik, 2026)
Purpose: This study analyzes systemic educational inequalities in Pagedongan and Pandanarum Districts, Banjarnegara Regency, using John Rawls’s theory of justice. It focuses on disparities in teacher distribution, infrastructure, funding allocation, and student transitions during the 2017–2024 period.Methodology: A qualitative case study approach was employed, involving participatory observation, semi-structured interviews with teachers, government officials, and parents, as well as document analysis of BPS data and educational budget reports. The data were analyzed thematically and validated through triangulation.Results: The findings reveal significant educational disparities, including a 7:1 ratio of primary schools to junior secondary schools, teacher shortages of up to 32% in certain rural areas, and an education budget absorption rate of only 47.5%. Economic barriers, such as transportation costs reaching IDR 500,000 per month, and sociocultural factors, including child labor and early marriage, which account for 65% of dropout cases, further exacerbate educational inequality. These conditions are inconsistent with Rawls’s difference principle, which emphasizes benefits for the least advantaged members of society. Conclusions: This study advocates affirmative policy measures, including a 50% increase in teacher incentives for service in remote areas, as well as reforms to decentralized educational governance. It offers a justice-based framework for addressing rural educational disparities in Indonesia.Limitations: The focus on only two districts may limit the generalizability of the findings. Furthermore, the qualitative design may not fully capture the statistical magnitude of educational inequalities. Developments occurring after 2024 were not considered, and Rawls’s theory may not entirely reflect local sociocultural dynamics.Contributions: This research provides both a philosophical framework and empirical evidence for policymakers. It identifies key drivers of educational inequality and proposes actionable recommendations for structural reform to ensure equitable educational opportunities for rural communities.